Using the History of Circle and Parabolic Segment Areas as Learning Alternatives in Integral - Yuwono, Layli Rahmania; Lindiarni, Janny; Afgani, Rizal (Universitas Negeri Semarang, 2024)
This article will present some classic problems in the Ancient Greece period: the ratio of the areas of two circles problem solved by Eudoxus and the area of a parabola segment problem solved by Archimedes. These problems can be used as alternative teaching resources to give the students an early understanding of the integral concept. This article focuses on finding alternatives for teaching integral material through theorems and historical understanding without calculus knowledge. This study used a systematic literature review method to analyze the mathematical content and the historical influences on their problem-solving methods. The literature sources were indirect sources such as journals, books, and other written literature. The results show that Eudoxus' principle has been a special limit problem since the period, helping solve the ratio of the areas of two circles problem, and there has been a special case of infinite geometric series solving the area of parabolic segment problem. This article gives some recommendations for the teachers at the end of the article, on how to give a representation of the propositions discussed in this article to the students so the students can understand the connections between the prior area problem (in which the area is bounded by its line segments) and the integral concept which will be learned.